2012
DOI: 10.1007/s00018-012-1223-y
|View full text |Cite
|
Sign up to set email alerts
|

Brain response to calorie restriction

Abstract: Calorie restriction extends longevity and delays ageing in model organisms and mammals, opposing the onset and progression of an array of age-related diseases. These beneficial effects also extend to the maintenance of brain cognitive functions at later age and to the prevention, at least in rodents, of brain senescence and associated neurodegenerative disorders. In recent years, the molecular mechanisms underlying brain response to calorie restriction have begun to be elucidated, revealing the unanticipated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 167 publications
0
40
0
Order By: Relevance
“…Administration of RAs induces many of the beneficial effects observed after DR. DR is able to ameliorate age-related insulin resistance and degenerative brain diseases, and similar results have been described after treatment with RAs343536. Both DR and administration of RAs are able to protect from ischemic stroke in the brain373839. Signaling pathways activated by the interaction between RAs and nuclear receptors have also been considered to have tumor-, and immune suppressive effects, just as DR93340.…”
Section: Discussionmentioning
confidence: 61%
“…Administration of RAs induces many of the beneficial effects observed after DR. DR is able to ameliorate age-related insulin resistance and degenerative brain diseases, and similar results have been described after treatment with RAs343536. Both DR and administration of RAs are able to protect from ischemic stroke in the brain373839. Signaling pathways activated by the interaction between RAs and nuclear receptors have also been considered to have tumor-, and immune suppressive effects, just as DR93340.…”
Section: Discussionmentioning
confidence: 61%
“…Finally, there is CR, a dietary practice known to reduce the progression of many age-related diseases. Interestingly, this particular dietary strategy, which the KD was originally designed to mimic, has been an intense focus for researchers interested in the mechanisms underlying aging/longevity, neurological diseases, and a host of other conditions (58)(59)(60).…”
Section: Variations On the Kdmentioning
confidence: 99%
“…Animal studies have shown that daily CR, intermittent fasting (IF), and alternate day fasting (ADF) not only modify the nutrient sensing pathways in the brain (Figure 2) but also increase synaptic plasticity, neurogenesis and neuroprotection (Fusco and Pani, 2013). CR and IF delay features of aging both on the microscopic and global levels (Pani, 2015).…”
Section: Unraveling the Relationships Among Calorie Restriction Lmentioning
confidence: 99%